Persepsi Mahasiswa UIN Walisongo Terhadap Covid-19 Dan Perilaku Kesehatan - Shela Delfia Ramadhana; Dian Fadlilati; Ahmad Fauzan Hidayatullah; Bunga Ihda Norra; Anif Rizqianti Hariz (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2021)
Covid-19 is a disease caused by the coronavirus. Since the end of 2019, WHO has reported cases of pneumonia that occurred in Wuhan, Tiongkok, which then spread to several countries including Indonesia. The number of the spread of Covid-19 is increasing day by day, the government continues to try to break the chain of the spread of Covid-19. The success of efforts to break the Covid-19 chain depends on the public's knowledge and perception of Covid-19 and its prevention efforts. This study aims to determine the perceptions and behavior of UIN Walisongo students in preventing Covid-19. This study used a quantitative descriptive research method, with a data collection instrumen in the form of a questionnaire. Data collection techniques using a google form questionnaire with 10 statements and opinions from UIN Walisongo students. The study population was all students of UIN Walisongo Semarang and as a sample were 302 students from various faculties who were selected by nonprobability sampling. The results showed 86.49% of the students of UIN Walisongo have a